Against the Asymmetric Convergence Model of Public Justification - Boettcher, James W. (Ethical theory and moral practice, 2015)
Compared to standard liberal approaches to public reason and justification, the asymmetric convergence model of public justification allows for the public justification of laws and policies based on a convergence of quite different and even publicly inaccessible reasons. The model is asymmetrical in the sense of identifying a broader range of reasons that may function as decisive defeaters of proposed laws and policies. This paper raises several critical questions about the asymmetric convergence model and its central but ambiguous presumption against coercion. By drawing on the theory of structural coercion, a main conclusion of the paper is that the asymmetric convergence model ultimately encounters the very incompleteness problems that its proponents often associate with more familiar consensus models of public justification. The paper also develops an alternative, Rawlsian-inspired account of public justification that includes elements of both convergence and consensus but not asymmetry. The Rawlsian model enables us to understand how democratic decisions may possess a degree of procedural, but still morally significant, liberal legitimacy under conditions of pluralism even when citizens fail to agree fully about either the premises of or conclusions to their political arguments.